Ben-Gurion and the Palestinian Refugees: Ideology, Morality, and Praxis. Issue 1 (1st March 2020) - Goldstein, Yossi
Abstract: A prominent aspect of the Jewish-Arab conflict over Palestine has been the Palestinian 'catastrophe' or 'Nakba'—the displacement of some 750, 000 Palestinians during Israel's War of Independence. David Ben-Gurion, the Yishuv's pre-state leader and Israel's first prime minister, was an influential figure in this process. This article investigates Ben-Gurion's attitude toward the Palestinian refugee problem, highlighting its dynamic nature and its linkage to military developments. Contrary to the conclusions of previous research, only after the Arab states' invasion and the war's expansion in late May and early June 1948 did Ben-Gurion decide to oppose the refugees' return. Undeterred by his own ethical misgivings and international efforts to secure repatriation, his view was reinforced over time, as Israel's victories on the battlefield became unequivocal.